2018
DOI: 10.24914/jeb.v21i1.1039
|View full text |Cite
|
Sign up to set email alerts
|

Exploring government internet financial reporting in Indonesia

Abstract: Government financial reporting as public accountability and transparency is important. Previous research show that almost all local government in Indonesia have their official website, which is active use as presenting news, local potentials, and local government services. Unfortunately, there are still limited local governments which are disclose their financial information as well as budgeting reports and financial statements on their websites. This research aims to explore whether political competition, loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…(Rulitawati et al, 2020) concluded that long-term solvency, including leverage, is the aspect of financial condition considered most important by users of government financial statements. However, different results are found in research (Diptyana, 2018) which states that Leverage has no effect on Internet Financial Reporting.…”
Section: Introductionmentioning
confidence: 75%
“…(Rulitawati et al, 2020) concluded that long-term solvency, including leverage, is the aspect of financial condition considered most important by users of government financial statements. However, different results are found in research (Diptyana, 2018) which states that Leverage has no effect on Internet Financial Reporting.…”
Section: Introductionmentioning
confidence: 75%
“…Afryansyah (2013) mengungkapkan bahwa jumlah kepadatan penduduk suatu daerah tidak cukup untuk memengaruhi publikasi laporan keuangan oleh pemerintah daerah secara sukarela melalui internet. Website pemerintah daerah lebih digunakan sebagai media pemberitahuan kepada publik terkait hal-hal di luar data keuangan pemerintah daerah itu sendiri, misalnya sebagai bentuk publikasi kegiatan pemerintah dan pencapaian nonkeuangan pemerintah daerah (Diptyana & Rokhmania, 2018).…”
Section: Pendahuluanunclassified
“…An increase in own-source revenue is always carried out to motivate local governments to be able to finance their own needs, so as to be independent and no longer depend on the central government. Based on the stewardship theory, local governments can show their responsibility for good performance through a large amount of regional wealth and resources, making them try to write better financial statements [17].…”
Section: Regional Wealthmentioning
confidence: 99%